1999
DOI: 10.1074/jbc.274.22.15297
|View full text |Cite
|
Sign up to set email alerts
|

IKKγ Mediates the Interaction of Cellular IκB Kinases with the Tax Transforming Protein of Human T Cell Leukemia Virus Type 1

Abstract: The Tax oncoprotein of human T cell leukemia virus type 1 constitutively activates transcription factor NF-B by a mechanism involving Tax-induced phosphorylation of IB␣, a labile cytoplasmic inhibitor of NF-B. To trigger this signaling cascade, Tax associates stably with and persistently activates a cellular IB kinase (IKK) containing both catalytic (IKK␣ and IKK␤) and noncatalytic (IKK␥) subunits. We now demonstrate that IKK␥ enables Tax to dock with the IKK␤ catalytic subunit, resulting in chronic IB kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 31 publications
7
145
0
Order By: Relevance
“…It has been shown that NEMO interacts with IKK subunits through the N-terminal part of its CC1, whereas the C-terminal part of this domain provides a binding site for Tax or RIP. 7,8 In addition, the CC2/ LZ part of NEMO represents the minimal oligomerization domain of the molecule. 9 Finally, the NEMO ZF appears required for IKK activation in response to TNF, LPS or IL-1 10 although its exact function remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that NEMO interacts with IKK subunits through the N-terminal part of its CC1, whereas the C-terminal part of this domain provides a binding site for Tax or RIP. 7,8 In addition, the CC2/ LZ part of NEMO represents the minimal oligomerization domain of the molecule. 9 Finally, the NEMO ZF appears required for IKK activation in response to TNF, LPS or IL-1 10 although its exact function remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence suggests that the assembly of a transcriptionally competent 'nuclear' Tax-NF-kB-CBP complex likely first occurs in the cytoplasm (Azran et al, 2005). One prevailing view is that Tax binds the IKKg/ NEMO molecule in the cytoplasm to influence the activity of the IKKa/IKKb/IKKg complex (Chu et al, 1999;Harhaj and Sun, 1999;Jin et al, 1999a). Activated IKKa/ IKKb/IKKg complexes then phosphorylate IKKa/b leading to a cascade of events (reviewed elsewhere in this issue by Sun and Yamaoka) which result in nuclear migration of NF-kB (Iha et al, 2003).…”
Section: Structure-function Features Of Tax For Transcriptional Activmentioning
confidence: 99%
“…In HTLV-I-transformed T cells, Tax is stably assembled into the canonical IKK complex, in which IKK remains chronically phosphorylated and activated (Chu et al, 1998;Carter et al, 2001). The Tax/ IKK complex formation relies on physical interaction between Tax and the IKK regulatory subunit, IKKg (Chu et al, 1999;Jin et al, 1999). Tax appears to directly target IKKg, since these two proteins interact in both mammalian cells (Chu et al, 1999;Jin et al, 1999) and yeast cells (Jin et al, 1999).…”
Section: Adaptor Function Of Ikkc In Tax-mediated Activation Of Ikkmentioning
confidence: 99%
“…The Tax/ IKK complex formation relies on physical interaction between Tax and the IKK regulatory subunit, IKKg (Chu et al, 1999;Jin et al, 1999). Tax appears to directly target IKKg, since these two proteins interact in both mammalian cells (Chu et al, 1999;Jin et al, 1999) and yeast cells (Jin et al, 1999). The Tax/IKKg interaction is required for recruiting Tax to the IKK catalytic subunits and for Tax-mediated activation of IKK .…”
Section: Adaptor Function Of Ikkc In Tax-mediated Activation Of Ikkmentioning
confidence: 99%